Monte Carlo study of the evolution of diffuse scattering and coherent modulation during h.c.p. to f.c.c. martensitic transition - I. Infinitely strong repulsive interaction model - Shrestha S.P.; Tripathi V.; Kabra V.K.; Pandey D. (My University, 2025)
Calculation of diffuse scattering during h.c.p. to f.c.c. martensitic transition by non-random insertion of deformation faults using a Monte Carlo technique is presented. It is shown that a coherent modulation of wavelength λ = 6dm can result during such transitions. The intensity and sharpness of the satellite peaks are shown to depend on the volume fraction of the twin-related f.c.c. variants. The predicted satellite peaks are in good agreement with those observed in Co and Co-Ni single crystals undergoing h.c.p. to f.c.c. martensitic transition. Copyright © 1996 Acta Metallurgica Inc.